PENGARUH MODEL PEMBELAJARAN PARTISIPATIF TERHADAP MOTIVASI BELAJAR WARGA BELAJAR PKBM HANDAYANI KECAMATAN ULAWENG KABUPATEN BONE - ramadhani, khaerani; marzuki, kartini; Muhaemin, Muhaemin B (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
This research aims to determine whether or not there is an influence of the participatory learning model on the learning motivation of residents studying in PKBM Handayani, Ulaweng District, Bone Regency. The sample from this research was 30 people. Data collection was carried out using questionnaires and documentation methods. The techniques used in data analysis are descriptive frequency analysis, data normality, and simple linear regression. Based on the research results, it shows that there is a significant relationship between the influence of the participatory learning model on the learning motivation of residents studying in PKBM Handayani, Ulaweng District, Bone Regency.